Perceptions of patient-centred care at public hospitals in Nelson Mandela Bay - Sihaam Jardien-Baboo; Dalena van Rooyen; Esmeralda Ricks (AOSIS, 2016)
In South Africa, the quality of health care is directly related to the concept of patient-centred care and the enactment of the Batho Pele Principles and the Patients' Rights Charter. Reports in the media indicate that public hospitals in the Eastern Cape Province are on the brink of collapse, with many patients being treated in condemned hospitals which lacked piped water, electricity and essential medical equipment. Receiving quality care, and principally patient-centred care, in the face of such challenges is unlikely and consequently leads to the following question: "Are patients receiving patient-centred care in public hospitals?" A qualitative, explorative, descriptive and contextual study was conducted to explore and describe the perceptions of professional nurses regarding patient-centred care in public hospitals in Nelson Mandela Bay. Semi-structured interviews were conducted with a total of 40 purposively selected professional nurses working in public hospitals in Nelson Mandela Bay, Eastern Cape Province. Interviews were analysed according to the method described by Tesch in Creswell (2009:192). Professional nurses perceive patient-centred care as an awareness of the importance of the patient's culture, involving the patient's family, incorporating values of love and respect, optimal communication in all facets of patient care and accountability to the patient. Factors which enable patient-centred care were a positive work environment for staff, nursing manager's demonstrating exemplary professional leadership, continuous in service education for staff and collaborative teamwork within the interdisciplinary team. Barriers to patient-centred care were a lack of adequate resources, increased administrative work due to fear of litigation and unprofessional behaviour of nursing staff.